2021
DOI: 10.3389/fendo.2021.778737
|View full text |Cite
|
Sign up to set email alerts
|

Life-Time Environmental Chemical Exposure and Obesity: Review of Epidemiological Studies Using Human Biomonitoring Methods

Abstract: The exponential global increase in the incidence of obesity may be partly attributable to environmental chemical (EC) exposure. Humans are constantly exposed to ECs, primarily through environmental components. This review compiled human epidemiological study findings of associations between blood and/or urinary exposure levels of ECs and anthropometric overweight and obesity indices. The findings reveal research gaps that should be addressed. We searched MEDLINE (PubMed) for full text English articles publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 186 publications
(396 reference statements)
0
7
0
Order By: Relevance
“…Throughout our lifetime, chronic exposure to obesogens is likely the primary cause of obesity and metabolic disorders (Trasande et al., 2016 ). Some obesogens (e.g., bisphenols and phthalates) are lipophilic, accumulating in the adipose tissue of obese women and changing their chromatin organization and structure to influence the development of obesity in their offspring (Mohanto et al., 2021 ). Microplastics can induce oxidative stress and affect adipocyte differentiation following accumulation in liver and kidney, altering the energy balance and lipid metabolism (Kannan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout our lifetime, chronic exposure to obesogens is likely the primary cause of obesity and metabolic disorders (Trasande et al., 2016 ). Some obesogens (e.g., bisphenols and phthalates) are lipophilic, accumulating in the adipose tissue of obese women and changing their chromatin organization and structure to influence the development of obesity in their offspring (Mohanto et al., 2021 ). Microplastics can induce oxidative stress and affect adipocyte differentiation following accumulation in liver and kidney, altering the energy balance and lipid metabolism (Kannan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microplastics can induce oxidative stress and affect adipocyte differentiation following accumulation in liver and kidney, altering the energy balance and lipid metabolism (Kannan et al., 2021 ). Furthermore, additives and monomers cause indirect toxicity for humans by promoting adipogenesis and lipid accumulation (Mohanto et al., 2021 ). A previous study demonstrated that chlorophenol, another environmental pollutant, was positively associated with central obesity in Korean girls.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 140 , 142 , 143 , 160–162 The exposure levels of humans to environmental chemicals are generally estimated by biomonitoring of these chemical’s essential compounds or metabolites in human urine or blood as exposure biomarkers. 163 DNA adducts of acrylamide might be used as biomarkers for monitoring chronic internal exposure to acrylamide. 164 In addition, hemoglobin adducts of acrylamide (HbAA) and its metabolite glycidamide (HbGA) can also be considered as biomarkers of exposure.…”
Section: Acrylamide As a Controversial Obesogenic Compoundmentioning
confidence: 99%
“…The WHO and others proposed that various sources of chemical exposure need to be associated with negative health outcomes (Naidu et al 2021 ; Prüss-Ustün et al 2011 ; WHO 2016 ). Potential human health effects due to exposure to chemicals have, for instance, been discussed for neurodevelopmental disorders (Bennett et al 2016 ), obesity (Mohanto et al 2021 ) or male reproductive health (Foresta et al 2018 ; Pollard et al 2019 ; Wu et al 2022 ).…”
Section: Evidence For Sufficient Protection Of Human Health Regarding...mentioning
confidence: 99%